THE EFFECT FIRM SIZE ON COMPANY VALUE WITH PROFITABILITY AS INTERVENING VARIABLE AND DIVIDEND POLICY AS MODERATING VARIABLE - Suci Atiningsih; Khairina Nur Izzaty (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine the effect of firm size on firm value with profitability as an intervening variable and dividend policy as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The population in this study were 306 manufacturing companies listed on the Indonesia Stock Exchange. Sampling using purposive sampling technique. The sample of this research is manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. This study uses secondary data. Data analysis used linear regression with path analysis. The results of this study are firm size has a positive effect on ROA and ROE. Firm size, ROA, and ROE have a positive effect on firm value. Profitability can mediate the effect of firm size on firm value and dividend policy can moderate the effect of firm size on firm value.